1990
DOI: 10.1002/1097-0142(19900801)66:3<610::aid-cncr2820660335>3.0.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Cancer patient satisfaction with care

Abstract: A diagnosis of cancer places considerable stress on patients and requires them to make major adjustments in many areas of their lives. As a consequence, considerable demands are placed on health care providers to satisfy the complex care needs of cancer patients. Currently, there is little available information to indicate the extent to which cancer patients are satisfied with the quality of care they receive. The present study assessed the perceptions of 232 ambulatory cancer patients about the importance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
133
1
2

Year Published

1997
1997
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(150 citation statements)
references
References 26 publications
11
133
1
2
Order By: Relevance
“…Another may be that the patients' ability to comprehend and the desire to obtain information was truly underestimated. The latter explanation is in accordance with the finding by others suggesting that physicians have difficulties in estimating the amount and type of information that patients want and their effectiveness in imparting information (Blanchard et al, 1988;Mackillop et al, 1988;Wiggers et al, 1990).…”
Section: Resultssupporting
confidence: 91%
“…Another may be that the patients' ability to comprehend and the desire to obtain information was truly underestimated. The latter explanation is in accordance with the finding by others suggesting that physicians have difficulties in estimating the amount and type of information that patients want and their effectiveness in imparting information (Blanchard et al, 1988;Mackillop et al, 1988;Wiggers et al, 1990).…”
Section: Resultssupporting
confidence: 91%
“…However, a common source of illness uncertainty is a lack of information about the nature, course, and prognosis of the disease. 42 A number of investigations of communication between physicians and patients revealed communication problems that generated informational uncertainty. Uncertainty about disease status and disease containment appears to increase when the benefits from treatment are discussed in terms of statistics and probabilities, an approach commonly used by physicians when talking with newly diagnosed patients.…”
Section: Patient-provider Communicationmentioning
confidence: 99%
“…They claim that it is a complex, multidimensional variable, which does not yet have an adequate theoretical formulation (Avis, Bond, & Arthur, 1995;Carr-Hill, 1992;Strasser, Aharony, & Greenberger, 1992). Others have noted that global ratings of patient satisfaction with medical care tend to be quite high, to be lacking in variability, and to be generally unrelated to efficacy of intervention or patient psychological adjustment (Baider, Uziely, & De-Nour, 1997;Oberst, 1984;Wiggers et al, 1990). In this light, perhaps it should not be surprising that we found patient satisfaction with the cancer diagnostic consultation to be unrelated to patients' subsequent psychological distress.…”
mentioning
confidence: 60%
“…In particular, it may be important to differentiate between patients' perceptions of their physicians' technical competence during the interview and perceptions of the physicians' skill in managing the interpersonal aspects of the communication (e.g., emotional supportiveness and caring). Previous research has suggested that medical patients are capable of distinguishing among physicians' interpersonal, communication, and technical skills, and that these are among the most important dimensions for determining patients' perceptions of the quality of medical care (Cockburn et al, 1991;Di Matteo & Hays, 1980;Thorn & Campbell, 1997;Wiggers, O'Donovan, Redman, & Sanson-Fisher, 1990). Although research has documented the relative importance of these three factors for patient outcomes such as satisfaction (Wiggers et al), trust in the physician (Thorn & Campbell, 1997), and compliance with medical recommendations (Willson & McNamara, 1982), no research to date has compared the importance of these factors with regard to patients' psychological adjustment.…”
Section: Discussionmentioning
confidence: 99%